Artikel PENGARUH PROFITABILITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG - Karnawati, Yosevin; Ika Kartika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of profitability, solvency, and firm size on audit report lag. The population in this study are all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique used purposive sampling, so the number of research samples was 65 data. The research method uses multiple linear regression analysis, F test and t test. F test results show that profitability, solvency, and firm size have a simultaneous effect on audit report lag. Partially, profitability and firm size have no effect on audit report lag, but solvency has a positive effect on audit report lag. The coefficient of determination (R²) in this study was 11.7%. The research findings show that the average financial report submission time is 84 days